Development of a low-cost greenhouse for 3D printer filaments (Research, Society and Development, 2023)
3D printing technology has been widely researched for improvement around the world, as it is a relatively new technology that allows the printing of geometries that other manufacturing processes did not allow. Most printers on the market today are of the FDM type, which uses sensitive filaments to make impressions. This research is characterized as an experimental study, in which the objective was to build a prototype that uses the low cost PID system, capable of reaching 50 °C and of high thermal resistance. In this perspective, the objective of the study is defined by investigating the possibilities of developing a low-cost greenhouse for 3D printer filaments. It is considered that the objective of the research was achieved, since the performance that the prototype achieved was very satisfactory due to the low cost invested and because it is a new area that the group is exploring. It was also verified that the PID control makes the process much more precise since without it, the system becomes more unstable, being able to interfere, for example, in industrial processes. Through the study carried out, knowledge was also acquired about heat transfer, electronics and programming, which is important to consider, because to carry out this type of experiment, consequently, it is based on theoretical knowledge so that the practice works correctly, and in the case of this study, both theory and practice could be improved.